Nuvole di punti semantiche - Remondino, Fabio; Ozdemir, Emre; Grilli, Eleonora (GEOmedia, 2019)
Point clouds, generated by photogrammetry or laser scanning, mainly contain geometric information. This makes them not very useful for different applications. Artificial Intelligence methods have opened up a new area of research and development, providing automatic solutions for segmentation and classification purposes.